Coincidental Bladder Cuff Transitional Cell Carcinoma in Nephroureterectomy Specimens: Risk Factors, Prognosis and Clinical Implementation - Elawdy, Mohamed Mohamed; Osman, Yasser; Taha, Diaa-Eldin; El-Halwagy, Samer; El-Mekresh, Mohsen (Urology Journal, 2018)
Purpose: There is a lack of reporting of the bladder cuff pathology in the literature and ongoing debate regarding the role of bladder cuff excision (BCE) in the prognosis in patients with upper tract urothelial carcinoma (UTUC). We aimed to know the risk factors, the survival, and the clinical course of such pathology. Materials and Methods: The study was retrospective, from 1983-2013 on 305 patients who had diagnosed with UTUC. Patients were managed by radical open/ laparoscopic nephroureterectomy with bladder cuff excision. The tumor was staged using 1997 TNM classification and the 3-tiered WHO grading system was used for grading. Patients who found to have a malignant bladder cuff on the final pathology were further analyzed for the risk factors for such disease and its effect on survivaltheir outcomes. Results: 13/ 281 (4.6%) cases were found to have malignant bladder cuff. Regarding tumor stage; one case was diagnosed with Tis, eight had T1 and four cases had T2 malignant bladder cuff. All cases were with pure ureteric or multifocalcentric tumors, and none had pure pelvicalyceal tumors (p = .001). Local recurrence at the surgical site and distant metastasis were significantly higher among patients with malignant bladder cuff (p = .001 and .002 respectively), and the last sustained its significance in multivariate analysis. Those patients had a poor prognosis when compared to non-malignant bladder cuff cases (Log Rank test, p = .001) Conclusion: Ureteric tumor is the only independent risk factor for malignant bladder cuff at the final pathology and is associated with increased risks for invasive bladder tumor, distant metastasis and poor survival in comparison with non-malignant bladder cuff. In a clinical implementation, BCE is considered as a mandatory step in management of ureteric tumors, while it could be omitted in pure and low grade renal pelvis tumors.